Theoretical Effect of Coma and Spherical Aberrations Translation on Refractive Error and Higher Order Aberrations - Arba-Mosquera, Samuel; Verma, Shwetabh; Awwad, Shady T. (Photonics, 2020)
(1) Background: The purpose of the study is to present a simple theoretical account of the effect of translation of coma and spherical aberrations (SA) on refractive error and higher order aberrations. (2) Methods: A computer software algorithm was implemented based on previously published methods. The effect of translation (0 to +1 mm) was analyzed for SA (0 to +2 µm) and coma (0 to +2 µm) for a circular pupil of 6 mm, without any rotation or scaling effect. The relationship amongst Zernike representations of various aberrations was analyzed under the influence of translation. (3) Results: The translation of +0.40 µm of SA (C[4,0]) by +0.25 mm with a pupil diameter of 6mm resulted in induction of tilt (C[1,1]), −0.03D defocus (C[2,0]), +0.03D astigmatism (C[2,2]) and +0.21 µm coma (C[3,1]). The translation of +0.4 µm of coma (C[3,1]) by +0.25 mm with a pupil diameter of 6 mm resulted in induction of tilt (C[1,1]), −0.13D defocus (C[2,0]) and +0.13D astigmatism (C[2,2]). A theoretical quantitative relationship between SA, coma, astigmatism and defocus is presented under the influence of translation. (4) Conclusion: The results can act as a guide for the clinician, in order to readily assess theoretical impact of wavefront map translation from pupil center to the visual axis. The resultant refractive coupling has to be taken into consideration especially when treating eyes with an abnormal corneal shape and/or large pupil center to corneal vertex chord.